2023
DOI: 10.1007/s10661-022-10807-0
|View full text |Cite
|
Sign up to set email alerts
|

Attaining freshwater and estuarine-water soil saturation in an ecosystem-scale coastal flooding experiment

Abstract: Coastal upland forests are facing widespread mortality as sea-level rise accelerates and precipitation and storm regimes change. The loss of coastal forests has significant implications for the coastal carbon cycle; yet, predicting mortality likelihood is difficult due to our limited understanding of disturbance impacts on coastal forests. The manipulative, ecosystem-scale Terrestrial Ecosystem Manipulation to Probe the Effects of Storm Treatments (TEMPEST) experiment addresses the potential for freshwater and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Pulse inundation events drove variation in soil heterotrophic CH 4 uptake, echoing our results for CO 2 release. Soil heterotrophic CH 4 uptake was negatively related to VWC and was responsible for the transient decrease in the forest soil CH 4 sink following saturation of the entire 0-30 cm soil profile (Hopple et al, 2023). Koide et al (2010) reported similar declines in CH 4 uptake that were attributed to soil saturation from extreme precipitation creating anoxic conditions and limiting CH 4 oxidation.…”
Section: Source Sensitivity To Episodic Environmental Changementioning
confidence: 89%
See 3 more Smart Citations
“…Pulse inundation events drove variation in soil heterotrophic CH 4 uptake, echoing our results for CO 2 release. Soil heterotrophic CH 4 uptake was negatively related to VWC and was responsible for the transient decrease in the forest soil CH 4 sink following saturation of the entire 0-30 cm soil profile (Hopple et al, 2023). Koide et al (2010) reported similar declines in CH 4 uptake that were attributed to soil saturation from extreme precipitation creating anoxic conditions and limiting CH 4 oxidation.…”
Section: Source Sensitivity To Episodic Environmental Changementioning
confidence: 89%
“…In our study, the resistance of root‐and‐rhizosphere CO 2 flux to changing soil VWC buffered soil heterotrophic impacts on total CO 2 flux, as demonstrated by the relatively rapid recovery of total CO 2 flux following episodic inundation events. Soil heterotrophs may have been more sensitive to episodic change because they are in surficial litter and soil where the greatest impacts of pulse inundation events occurred (Hopple et al., 2023), while plants have deep root systems that may require larger and/or prolonged moisture pulses that penetrate the soil profile to trigger physiological responses (Ogle & Reynolds, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a model-EME context, this allows the models to be evaluated at multiple treatment levels, circumventing the step change issues. Large, full ecosystem level experiments with sometimes groundbreaking treatments such as the TEMPEST flooding experiment (Hopple et al, 2023), are also not replicated but provide invaluable insights into ecosystem functioning.…”
Section: New Data For Eme-model Synthesismentioning
confidence: 99%